Self-Access Centre (SAC) in English Language Learning - Priyatmojo, Arif Suryo; Rohani, Rohani (Universitas Negeri Semarang, 2017)
Students of higher education in the global world need to have sufficient knowledge and skill in utilizing ICT (Information and Communication Technology) to face national and regional competition. To achieve this outcome, higher education (university) through its lower units - faculty and department can facilitate it through Self-Access Centre (SAC). English Department of Univeritas Negeri Semarang is one of the state universities in Central Java, Indonesia which has SAC used for academic purposes. This study is aimed at 1) finding benefits of SAC in a course ‗ICT in Language Learning‘, 2) reporting its benefits to promote independent learning, and 3) finding constraints faced in utilizing SAC. This study used qualitative approach employing SWOT analysis. The data is gained through three instruments: direct observation, interview, and study document. Two classes of ICT in Language Learning were taken as the objects of the study. The results showed that the students of the English Department gain benefits of SAC as they are facilitated with lots of facilities both software and hardware. Then, the students can also produce their own teaching media through utilizing available media independently. It can be seen from how the students can use free available online products such as Edmodo, Moodle, Skype, Wikispaces, Pbwork, and Tumblr with their creativities and modifications for learning objectives. Furthermore, SAC needs to have good management which involves not only from the department but also from faculty and university.